Borohydride reduction of azomethine bonds in β-alanine Schiff base complexes - (:unkn) unknown (My University, 2008)
Borohydride reduction of the azomethine bond in the Schiff base complexes of β-alanine has been studied. Ni(II), Pd(II) and Pt(II) complexes of N-β-carboxyethyl-2-hydroxynaphthyl-ideneimine (L1H2), N-β-carboxyethyl-2-hydroxybenzylideneimine (L2H2), and N-β-carboxyethyl-N-2-hydroxynaphtylmethyleneamine (L3H 2) have been prepared. L1H2 forms complexes with palladium as Pd(L1H)2, in which carboxylic groups do not participate in the coordination. L2H2 and L 3H2 behave as tridentate double charged ligands, giving complexes of the type ML2.nH2O and ML3.nH 2O. Ni(II) gives binuclear complex [NiL32H 2O]2. No visible reaction of -C=N- bond reduction with borohydride has been observed for the L1H2 complexes of Co(III) d6, Ni(II) d8, Pd(II) d8, Zn(II) d 10 ions at 25°C in dimethyl formamide. This tendency has also been observed for Ni(II) complex of salicylaldehyde based β-alanine Schiff base, L2H2, as well as Ni(II), Pd(II), Zn(II) complexes of salen. However, the C=N bond can be reduced with borohydride when it coordinates the metal ions, Cu(II), Co(II) and Mn(II). Ni(II) complexes of both Schiff bases are inactive against reduction. The reduction rates of Schiff bases and related activation energies have also been determined.